Legislative oversight and accountability of public finances : a case of Limpopo, Provincial Legislature for the period between 1994 and 2010 - Kgatjepe, Maaria Ishmael (University of Limpopo, 2018)
The Constitution of the Republic of South Africa of 1996 requires the Legislature in Local, Provincial and National Governments to hold the Executive accountable and continue to do oversight on the work of government. The Legislature in executing its work, sometimes make use of the Auditor General’s reports, Public Finance Management Act (PFMA) reports and all other reports submitted by constitutional institutions, the Executive and other agents of the State. The study investigates whether the Legislature understands its mandate as legislated and whether the legislation is efficient and effective in ensuring accountability and conducting oversight of the work of the Executive. The research methodology used in this study is the qualitative approach. The respondents were clear that the Legislature understand its business as legislated, and further that there is a challenge at implementation of these important functions of the Legislature. There is varying implementation due to resources, capacity constraints and lack of commitment. The study recommends that the training of Members of the Legislature and staff, allocation of adequate resources and proper planning. The commitment of the Members of the Executive to the process and implementation of consequence management for poor performance and key interventions to ensure efficient and effective oversight of public finances in the province
Thesis (MPA. (Public Administration)) -- University of Limpopo, 2018
Keywords: Public finance accountability; South African legislature; Oversight and accountability; Government accountability; Finance, Public - Auditing - Law and legislation - South Africa